Speaking Subskills in EFL Coursebooks - Katja Kranjec (Vestnik za Tuje Jezike, 2020)
The primary goal of most EFL students is to achieve fluency in the target language and become autonomous speakers who can react naturally in most situations. To achieve this, mastery of speaking subskills is crucial. The paper aims to identify how well specific subskills, i.e. negotiation of meaning and agenda management, are represented and developed in EFL coursebooks. Twenty coursebooks approved by the Slovene Ministry of Education, Science and Sport for 3rd and 4th year grammar school students are reviewed.